Hypothesis: determining phenotypic specificity facilitates understanding of pathophysiology in rare genetic disorders. Issue 4 (17th January 2020) - Haijes, Hanneke A.; Jaeken, Jaak; van Hasselt, Peter M.
Abstract: In the rapidly growing group of rare genetic disorders, data scarcity demands an intelligible use of available data, in order to improve understanding of underlying pathophysiology. We hypothesize, based on the principle that clinical similarities may be indicative of shared pathophysiology, that determining phenotypic specificity could provide unsuspected insights in pathophysiology of rare genetic disorders. We explored our hypothesis by studying subunit deficiencies of the conserved oligomeric Golgi (COG) complex, a subgroup of congenital disorders of glycosylation (CDG). In this systematic data assessment, all 45 reported patients with COG‐CDG were included. The vocabulary of the Human Phenotype Ontology was used to annotate all phenotypic features and to assess occurrence in other genetic disorders. Gene occurrence ratios were calculated by dividing the frequency in the patient cohort over the number of associated genes, according to the Human Phenotype Ontology. Prioritisation based on phenotypic specificity was highly informative and captured phenotypic features commonly associated with glycosylation disorders. Moreover, it captured features not seen in any other glycosylation disorder, among which episodic fever, likely reflecting underappreciated other cellular functions of the COG complex. Interestingly, the COG complex was recently implicated in the autophagy pathway, as are more than half of the genes underlying disorders that present with episodic fever. This suggests that whereas many phenotypic features in these patients are caused by disrupted glycosylation, episodic fever might be caused by disrupted autophagy. Thus, we here demonstrate support for our hypothesis that determining phenotypic specificity could facilitate understanding of pathophysiology in rare genetic disorders.